Exercício profissional em Secretariado sob a percepção dos acadêmicos do curso de Secretariado Executivo da Universidade Federal do Ceará - Santos, Marcia Helena da Costa (2013)
The Professional exercice involve many reasons to which it can be exercided for a satisfacty way. When a person choice a occupation, he must have in your mind your function and responsibility before to the society where he is inserted and which will be improve this your choice. For a professional exercice, be it regular or don’t regular, is necessary, over vocacion, capacitation across a formation which provide to the fellow intelectuals subsidies to a etical and conscious actuaction. In front this arguments and challenges to the professional exercice today, the principal objective this work is reflect about the Secretariat Executive’s students motivation about professional exercice. The search had like teoric referencials the immediate authors: Medeiros and Hernandes, Portela and Schumacher, Natalense, among others knowed authors secretarial’s area.The search have like reference the ample sense of the professional exercice and secretariat and so like the necessary formation. The methodology used in this search is qualitative, explorative, of camp, bibliographic e documental. To information’s collect was aplicated a questionary near the UFC Secretariat Executive’s. Was identify across the analyses of the informations colected which the student to hanker to practise the Secretariat Executive profession even the challenges and tabus of this profession.